The Holistic-Dialogical Paradigm of Mulyadhi Kartanegara: A Study of the Concept of Nature - Hidayat, Thaufiq (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2022)
Philosophers have long echoed various views about nature, but these concepts still reduce the meaning of nature itself. In recent developments, nature seems to be perceived as dead and has an identity that is very far from the side of human existence on earth. As a result, nature becomes the best and often becomes an outlet for human greed. Because of that, it is a crucial requirement to look at the latest perspective holistically in studying natural problems. This article discusses Mulyadhi Kartanegera’s holistic-dialogical paradigm in understanding the concept of nature. in answering research, data was collected through the works of Mulyadhi Kartanegara and supported by documents, books, and articles related to the object of research. The data that was collected was analyzed using descriptive-interpretative methods and holistic data analysis to get a conclusion. The research result show that nature in Mulyadhi Kartanegara’s holistic-dialogical paradigm is alive in the same sense as humans who have an awareness of intelligence and beauty. Various natural abilities, such as intelligence, can exceed human capacity. In this case, nature must be treated as a living system with self-control and regulation, called the sunnah of Allah.